Implementasi E-Katalog berbasis Knowledge Management Untuk Mendukung Keberlanjutan Industri Tenun Ikat Kabupaten Sumba Timur - Augustina Asih Rumanti; Muhammad Almaududi Pulungan; Mohammad Deni Akbar; Amelia Kurniawati; Mia Amelia; Artamevia Salsabila Rizaldi (Jurnal Pengabdian Masyarakat Charitas, 2026)
This community service activity aims to support the sustainability of the East Sumba ikat weaving industry through the implementation of a Knowledge Management-based e-Catalog as a means of preserving traditional knowledge while increasing market access. The East Sumba weaving industry faces various challenges, including a lack of documentation of techniques and symbolic meanings of motifs, limited digital literacy among artisans, and low utilization of technology in product marketing. The target of this activity is the weaving artisan community in Patawang Village, East Sumba Regency. The implementation method was carried out in a participatory manner through the stages of problem identification, data collection, design, and implementation of the e-Catalog using SECI (Socialization, Externalization, Combination, and Internalization) approach. Data were collected through in-depth interviews with senior artisans and traditional leaders, field observations, and documentation of the weaving process, motif philosophy, and history of ikat weaving. Tacit knowledge previously passed down orally was successfully transformed into explicit knowledge in the form of digital content in the form of text, photos, and product catalog structures. The results of the activity show that the e-Catalog functions not only as a promotional medium, but also as a structured documentation system for cultural knowledge. To ensure long-term sustainability, it is recommended that the e-Catalog be continuously developed and updated through active artisan involvement, integrated with digital marketing platforms, and supported by ongoing